Thermo-Economic Optimization and Life Cycle Analysis of Bio-Limestone Bricks Enriched with Eggshells for Buildings - Lajimi, Nour; Helel, Dalel; Boukadida, Noureddine (Salehan Institute of Higher Education, 2026)
Tunisia is confronted with dual challenges in its energy transition and the management of organic waste, where eggshells constitute a significant yet underutilized resource, with an annual production approximating 50,000 tons. This study presents an integrated thermo-economic and environmental assessment of bio-limestone bricks incorporating eggshell waste, addressing critical gaps in sustainable construction research. The primary objectives are to present the thermophysical properties of these innovative bricks, evaluate their energy performance at the building scale through dynamic simulation, and quantify their economic viability and environmental benefits. Using dynamic thermal simulation with TRNSYS software validated by analytical solutions for a building in a Mediterranean climate. The methodology combines energy modeling with detailed economic analysis and life cycle assessment to provide a holistic evaluation framework. Key findings reveal that bricks with 20% eggshell content reduce cooling loads by 50.9% (2648 W vs. 5400 W for conventional bricks), achieve annual energy savings of 81.5 TND with a favorable 1.23-year payback period, and reduce CO₂ emissions by 51%. The originality of this work lies in a complete energy and economic simulation and a simplified environmental assessment for building materials enriched with eggshells, providing both waste recovery strategies and energy efficiency of buildings in hot climates.